2017
DOI: 10.3354/dao03113
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of horizontal transmission of the cancer-associated Steamer retrotransposon among ecological cohort bivalve species

Abstract: Bivalve specimens from legacy frozen tissue collections, and others freshly obtained, were surveyed for the presence of the Steamer long terminal repeat (LTR)-retrotransposon associated with disseminated hemic neoplasia of the soft-shelled clam Mya areneria. Of 22 species investigated using primers for the pol region, only Atlantic M. arenaria, Atlantic and North Sea razor clams Ensis directus, and Baltic clams Macoma balthica from the North Sea were found to possess copies of Steamer in their genomes. Notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
4
3
0
3
Order By: Relevance
“…SLE sequences were present in 11 families and nine orders. A previous study of bivalves from the AMCC using highly specific primers (16) identified SLEs nearly identical to Steamer in two bivalves (Baltic clam, Limecola balthica, and Atlantic razor clam, Ensis directus), and we confirmed those findings using the degenerate primers.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…SLE sequences were present in 11 families and nine orders. A previous study of bivalves from the AMCC using highly specific primers (16) identified SLEs nearly identical to Steamer in two bivalves (Baltic clam, Limecola balthica, and Atlantic razor clam, Ensis directus), and we confirmed those findings using the degenerate primers.…”
Section: Resultssupporting
confidence: 89%
“…The finding of Steamer in both Pacific and European samples of M. arenaria suggests that the first transmission into the M. arenaria genome occurred at least 800 y ago, as M. arenaria is believed to have been brought to Europe around the 1300s (33). The Steamer sequences from the M. arenaria samples in this study and in 10 more studies published recently (16) are all nearly identical, again suggesting recent entry into the genome or a recent expansion of a single lineage within the species. The SLEs in cockles appear to be recently acquired as well.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The strongest evidence that this form of clams' neoplasia is transmissible comes from studies of unfiltered hemolymph that induce cancer in healthy individuals (14)(15). Subsequent studies were consistent with a retrovirus aetiology where the examination of the hemolymphatic transcriptome identified the presence of retroviral protease, RT and integrase (15)(16)(17). Surprisingly, the highest RT levels was detected in cultured hemocytes compared to cell-free extracts (18).…”
Section: Introductionsupporting
confidence: 57%